2010
DOI: 10.1177/1069072710382615
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Vocational Interests, Self-Efficacy, and Achievement in the Prediction of Educational Pathways

Abstract: The influence of vocational interest, self-efficacy beliefs, and academic achievement on choice of educational pathway is described for a cohort of Australian students. Participants were 189 students aged 14—15 years, who were considering either academic or applied learning pathways and subject choices for the final 3 years of secondary school. Using Holland’s interest model within a social cognitive career theory (SCCT) framework, logistic regression analyses indicated that all three constructs were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
2
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 39 publications
(52 reference statements)
0
30
2
8
Order By: Relevance
“…This contrasts to previous findings and is also somewhat surprising given that perceived behavioural control is considered by many to be akin to self-efficacy (e.g. Manstead and van Eekelen 1998), which has long been established as influential in students' educational choices (Betz and Hackett 1983;Lent, Frederick, and Bieschke 1991;Patrick, Care, and Ainley 2011). Indeed, the two items used to measure perceived behavioural control in the present study, that is, 'I am confident that if I wanted to I could study physics/ media studies at AS level (strongly agree-strongly disagree)' and 'For me, studying physics/media studies at AS level would be (impossible-possible)', are particularly synonymous with the concept of self-efficacy.…”
Section: Discussioncontrasting
confidence: 67%
“…This contrasts to previous findings and is also somewhat surprising given that perceived behavioural control is considered by many to be akin to self-efficacy (e.g. Manstead and van Eekelen 1998), which has long been established as influential in students' educational choices (Betz and Hackett 1983;Lent, Frederick, and Bieschke 1991;Patrick, Care, and Ainley 2011). Indeed, the two items used to measure perceived behavioural control in the present study, that is, 'I am confident that if I wanted to I could study physics/ media studies at AS level (strongly agree-strongly disagree)' and 'For me, studying physics/media studies at AS level would be (impossible-possible)', are particularly synonymous with the concept of self-efficacy.…”
Section: Discussioncontrasting
confidence: 67%
“…There is increasing empirical evidence that interest is a powerful catalyst for learning and academic development. A vast body of research shows positive effects of interest on student engagement at school, perceived task value, better academic achievements, and timely degree attainment in specific educational programs (Hidi 2006;Patrick et al 2011;Renninger and Hidi 2016;Tobias 1994). Moreover, interest is a significant factor in making sustainable choices in education and career (Eccles and Wigfield 2002;Harackiewicz et al 2008;Holmegaard 2015;Maltese and Tai 2010).…”
Section: Persons Pursuing Multiple Interests In Multiple Contextsmentioning
confidence: 99%
“…In much of the research on STEM careers, Social Cognitive Career Theory (SCCT) [7] has been the most widely used theoretical framework for empirical inquiry [8]. Empirical studies have shown that self-efficacy [9][10][11][12][13][14], interests [6,11,[15][16][17], course selection [14,16], STEM-related activities, school engagement [16,18], academic proficiencies, and familial background [16] are predictive of STEM-related career paths. In a recent qualitative study, Li, Mau, Chen, Lin, & Lin [19] identified four domains, personal input, contextual variables, outcome expectations, and self-efficacy, that were involved in the STEM career development of high-school students, which parallel with the SCCT theoretical framework.…”
Section: Introductionmentioning
confidence: 99%